Tomato Supply Chain and Logistics Management of an Economic Crop in Tai Ngoi Community - Nabchid, Chadarporn (International Journal of Psychosocial Rehabilitation, 2020)
this research focuses on the development and participation of communities to increase their farming economic capability through the integration of efficient supply chain management and logistics management for their crop production. The key objectives of the present study were to investigate and illustrate in a model the relationship linkages in the supply chain management and logistics management of a community crop, namely tomatoes, as an important economic plant for the Tao Ngoi community. The research study used a qualitative research methodology, with data collected from a survey conducted with questionnaires and from in-depth interviews the main research tools. Data was collected from in-depth interviews with farmers and tomato processors and other stakeholders, as well as from participatory observation, with an aim to study the linkages between the supply chain representing the farmers as growers and the tomato processors and downstream actors. It was found that there had been changes in the traditional supply chain toward a new more modern format, whereby the growers exchange information with stakeholders to know the needs of the market and consumers in the country in order to better plan the production according to advance orders and demand. The study of the relationships in the tomotoes supply chain covers the suppliers of the raw materials and the merchants/buyers, who select the raw tomatoes for the factory processing according to the needs of their customers. This study aimed to help farmers deliver good quality raw materials, on time, and in a safe manner. Operations in the supply chain management were assessed using the supply chain operations reference (SCOR) model.Index Terms—, ,